Pemanfaatan Acetobacter xylinum terhadap Peningkatan Kualitas Nata de Banana Skin (Utilization of Acetobacter xylinum to improve the quality of Nata de Banana Skin) - Harlis HARLIS; Pinta MURNI; Muswita MUSWITA (Universitas Jambi, 2015)
Banana (Musa sp.) is the most widely consumed fruits since the children age up to the elderly. This is because bananas have quite complete nutrient content such as carbohydrates, proteins, vitamins and minerals, making it beneficial for the human body. People normally only consume and discard any banana skin. Therefore; it needs solutions to deal with the banana peel waste. Banana peels contain high enough nutrients that are carbohydrate 18.5%, phosphorus 28 mg, water 72 g, and some other chemical substances. The high nutrient content on the banana peel is potential to be used as food, one of which is in the form of nata. Nata is a product of microbial fermentation using Acetobacter xylinum. Nata can be made from coconut water waste, liquid waste or waste bark out pineapple and banana peel waste (Nata de Banana Skin). This study aimed to determine the effect of various types of banana peels using A. xylinum on the quality of nata de banana skin. The results showed that different types of banana peel affect the quality of Nata de Banana Skin, both on its flavor and its yield of Nata de Banana Skin. The pisang raja skins give the most optimal results for nata thickness and also perform the best organoleptic values.